PENGARUH TEMPERATUR DAN IRADIASI TERHADAP INTERDIFUSI PARTIKEL BAHAN BAKAR JENIS U−7Mo/Al - Ajiriyanto, Maman Kartaman; Ginting, Aslina Br.; Supardjo; Boybul, Boybul (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
U−7Mo/Al alloy had great potential as research reactor fuel, but it had several disadvantages, such as, it can form a interaction layer at the interface during the process of fabrication and irradiation in a reactor. The research objective was determining the interaction layer that was caused by interdiffusion or diffusion couple of U−7Mo with AlMg2 alloy which was annealed at 500 °C and 550 °C for 24 hours. The observation of microstructure used a Scanning Electron Microscope (SEM) on diffusion couple sample which was heated at temperature of 500 °C had not seen the layer interaction or the formation of a new phase between particles of U−Mo and Al matrix, but heating treatment at 550 °C indicated that U−7Mo alloy had been interdiffusion with AlMg2 plate produced (U,Mo) Alx compound on the interfaces. It was evidenced by interdiffusion reaction analysis used DTA that showed that U−7Mo / Al alloy at 500 °C had good heat compatibility, but at temperatures upper than 550 °C it had been phase changed from a + d to a + g phase. The heating in DTA furnace up to 679.14 °C produced U(Al,Mo)x meta stable phase and then interdiffusion process with uranium molten formed layer interaction that formed UAlx compound agglomerates (UAl4, UAl3 and UAl2). Agglomerates was formed from the heating process which was similar to agglomerates that caused by irradiation. U−7Mo / Al Fuel alloy that had 58% burn up had been interdiffusion between U−7Mo with Al matrix produced U(Al,Mo)x metastable phase that turned into (U, Mo) Al7 layer, UMo2Al20 precipitates, (UMo)Al3−Al and formed a boundary or UAlx (UAl4, UAl3 and UAl2) agglomerates. The results of microstructure analysis used SEM and interdiffusion reactions used DTA was supported by the analysis of micro hardness used Vickers Hardness. The results of hardness analysis that was done to AlMg cladding and U−7Mo alloy (before and after heating) and diffusion couple of U−7Mo / Al samples with AlMg2 plate after heating at 550 °C were respectively 64.62 and 340.45 HV (before heating) and 52.34; 303.16 and 497.34 HV (after heating). Diffusion couple U−7Mo/Al with AlMg2 plate samples had the highest hardness value. This hardness difference showed that the interdiffusion test used diffusion couple produced a new compound (U, Mo) Alx in interface zone that had different character, but the formation of interaction layer is not expected in the fuel U−Mo / Al dispersion because micro hardness and density of (U, Mo) Alx compound’s layer was lower than the average density of U−7Mo/ Al alloy.